1997
DOI: 10.1063/1.872382
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a high-power aluminum-wire array Z-pinch implosion

Abstract: Annular Al-wire Z-pinch implosions on the Saturn accelerator ͓D. D. Bloomquist et al., Proceedings, 6th Pulsed Power Conference ͑Institute of Electrical and Electronics Engineers, New York, 1987͒, p. 310͔ that have high azimuthal symmetry exhibit both a strong first and weaker second x-ray burst that correlate with strong and weaker radial compressions, respectively. Measurements suggest that the observed magnetic Rayleigh-Taylor ͑RT͒ instability prior to the first compression seeds an mϭ0 instability obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 19 publications
(22 reference statements)
7
36
0
Order By: Relevance
“…If it retains this spread, hits the center near the experimentally observed 50 cm /psec, and if radiation is produced as plasma thermalizes on axis, a pulse duration of some 4 ns (2 mm/(0.5 mm/ns)) would be expected. This duration is close to the observed value for our highly symmetric 90-wire shots [4], and is the mechanism believed responsible for the observed pulse width.…”
Section: -supporting
confidence: 63%
See 2 more Smart Citations
“…If it retains this spread, hits the center near the experimentally observed 50 cm /psec, and if radiation is produced as plasma thermalizes on axis, a pulse duration of some 4 ns (2 mm/(0.5 mm/ns)) would be expected. This duration is close to the observed value for our highly symmetric 90-wire shots [4], and is the mechanism believed responsible for the observed pulse width.…”
Section: -supporting
confidence: 63%
“…The perturbation is typically an initial random density variation. With an appropriate choice for the magnitude of this random density perturbation, Jim Hammer [SI showed that the growth of the RT instability, and the resultant increase in the thickness of the plasma sheath at the time of stagnation, can account for the width of the radiation pulse measured for our 90-wire implosions [4]. The dependence of such RT growth on a wide range of initial sheath densities and radii has been studied by Darrell…”
Section: The Rayleigh-taylor Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…IOC), and higher and then lower ion velocities of the emitting plasma (Fig. 10D), as expected for a double implosion q ' [25]. Images of the x-ray emission from the imploding shell a few nanoseconds prior to the first implosion exhibit the classic bubble and spike structure associated with the RT instability.…”
Section: A Measurementsmentioning
confidence: 57%
“…Estimates indicated a drastic reduction of the total energy needed for compression and ignition to perhaps as little as ∼ 100 kJ. The compression could be done as in other ICF concepts by laser or particle beams [2 -5] or even by soft X-rays from electric pulse powered imploded arrays of thin wires [6]. For the fast ignitor, two petawatt lasers were originally proposed.…”
Section: Introductionmentioning
confidence: 99%